Ancestral relationship of greengram (Vigna uadiau) advance breeding lines developed in India - KATIYAR, P K; DIXIT, G P; SINGH, B B (The Indian Journal of Agricultural Sciences, 2011)
A study was conducted during 1996 to 2005 on the pedigrees of 413 greengram [Vigna radiata (L.) R. Wilczek] advanced breeding lines tested in initial varietal trials of AICRP on MULLaRP were traced back to 136 ancestors. ’Muzaffarpur local’ (Type 1) was the most frequently used parent, followed by ’T 49’, ’4453-3’, ’RUM S’, ’TPH 1’, ’Kundawa Baharaich’, ’Kopergaon’, ’P 23-67’, ’ML 23’ and ’Iranian local’. Extensive use of few ancestors led towards genetic erosion and narrowing of genetic base in greengram.